Bekerja dalam Perspektif Hadis - Wildan Afandi; Muhammad Alif (STIKes Ibnu Sina Ajibarang, 2025)
Working in Islam is not merely an economic activity, but rather a form of social and spiritual responsibility that becomes an act of worship when carried out with sincere intention and lawful means. The Qur’an and the sayings of Prophet Muhammad ﷺ encourage Muslims to be self-reliant, work diligently, and preserve their dignity by avoiding dependence on others. Core values such as honesty, responsibility, and perseverance serve as the foundation of Islamic work ethics. This study employs a qualitative method using a library research approach. Primary data are sourced from authentic hadith collections such as Sahih Bukhari and Sahih Muslim, while secondary data are obtained from relevant scholarly literature. Thematic (maudhu’i) analysis is used through steps including collection of work-related hadiths, thematic categorization, contextual interpretation, and correlation with contemporary life practices. The findings reveal that Islam greatly upholds the importance of work. Hadiths emphasizing the virtue of earning through one’s own labor, the superiority of the giving hand, the prohibition of begging without necessity, and the essential role of intention in work, form the moral and spiritual foundation for Muslims to regard work as a path toward honor, dignity, and the pleasure of Allah ﷻ.